2016
DOI: 10.1136/archdischild-2015-309813
|View full text |Cite
|
Sign up to set email alerts
|

Camp-based family treatment of childhood obesity: randomised controlled trial

Abstract: ObjectiveTo compare the effectiveness of a 2-year camp-based family treatment programme and an outpatient programme on obesity in two generations.DesignPragmatic randomised controlled trial.SettingRehabilitation clinic, tertiary care hospital and primary care.PatientsFamilies with at least one child (7–12 years) and one parent with obesity.InterventionsSummer camp for 2 weeks and 4 repetition weekends or lifestyle school including 4 days family education. Behavioural techniques motivating participants to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…For example, in Janicke et al 's [18] systematic review of randomised controlled trials, they excluded 54 of 278 papers selected for full-text review because they lacked appropriate control groups. Likewise, Benestad et al's [19] study noted a similar lack of adequate control groups in observational (i.e. non-experimental) weight-loss studies.…”
Section: Discussionmentioning
confidence: 92%
“…For example, in Janicke et al 's [18] systematic review of randomised controlled trials, they excluded 54 of 278 papers selected for full-text review because they lacked appropriate control groups. Likewise, Benestad et al's [19] study noted a similar lack of adequate control groups in observational (i.e. non-experimental) weight-loss studies.…”
Section: Discussionmentioning
confidence: 92%
“…Data collection occurred between April 2010 and June 2013. Details of the trial have been published previously 12…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported results of a 2-year randomised controlled trial (RCT) of a family summer camp treatment compared with an outpatient lifestyle intervention, finding no significant between-group differences after 2 years for primary outcomes (age-adjusted and sex-adjusted body mass index [BMI] SD score [BMI-SDS] for children’s and parents’ BMI) 12. However, these treatment options may still affect HRQoL differently.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the substantial efforts invested, the results of lifestyle programmes for young people have often been disappointing. A literature review suggests that, in many cases, participants register little change in their BMI by the end of the course (Benestad et al, 2016;Elvsaas, Juvet, Giske, & Fure, 2016;Ochner, Barrios, Lee, & Pi-Sunyer, 2013). A very similar pattern emerges in respect of lifestyle programmes targeting adults: whether in terms of participants reducing their BMI or managing to sustain such reductions in the long term, results have proved modest or negligible (Garner & Wooley, 1991;Ochner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis in this regard has been on family-oriented lifestyle interventions rather than childonly ones, in the expectation that targeting parents along with the child will serve to enhance treatment effectiveness. However, this assumption has been called into question by a recent randomized controlled trial comparing the results from a camp-based programme for families with those of an out-patient family-oriented treatment programme (Benestad et al, 2016). Benestad and colleagues found that the camp-based programme had "only small long-term effects on BMI (and some cardiovascular risk factors) in children with severe obesity", that "most children remained obese after treatment", and that it therefore seemed "unlikely that the high summer camp costs can be justified given the modest effects" (Benestad et al, 2016, p. 7).…”
Section: Introductionmentioning
confidence: 99%